The plasma separation card as a novel solution for enhancing central laboratory capability for HIV-1 viral load monitoring in limited-access settings. - Charles Kiyaga; Caroline Makoha; Ivan Nkugwa; Christopher Okiira; Richard Okwir; Sirak Zenebe Gebreab; Patricia Rodriguez-Ventosa Suarez; Benjamin LaBrot; Ana Carrasco Durán (Public Library of Science (PLoS), 2023)
Measurement of HIV-1 viral load (VL) is essential for monitoring antiretroviral treatment (ART) efficacy. The preferred specimen type for VL is plasma, but in remote settings where collection and preservation of plasma many not be possible, dried blood spots (DBS) are often used instead. A new specimen collection matrix, the cobas plasma separation card (PSC, Roche Diagnostics Solutions), enables specimen preparation from a finger prick or venous blood, using a multi-layer absorption and filtration design that results in a specimen similar to dried plasma. We sought to confirm the correlation between VL results obtained using PSC prepared from venous blood to those from plasma or DBS, as well as PSC prepared with capillary blood from a finger prick. PSC, DBS and plasma were prepared with blood from HIV-1 infected persons attending a primary care clinic in Kampala, Uganda. VL in PSC and plasma was measured using cobas HIV-1 (Roche Diagnostics), while VL in DBS was measured with RealTime HIV-1 (Abbott Diagnostics). The correlation between VL from plasma and PSC made from capillary or venous blood was high (regression coefficient of determination r2 between 0.87 and 0.91), and there was good agreement based on mean bias (-0.14 to 0.24 log10 copies/mL) and classification of VL above or below 1000 copies/mL (91.4% agreement). In contrast, VL from DBS was lower than plasma or PSC (mean bias 0.51 to 0.63 log10 copies/mL) and not as well correlated (r2 0.78 to 0.81, 75.1-80.5% agreement). These results confirm the utility of PSC as an alternative specimen type for HIV-1 viral load measurement in areas where preparation and optimal storage or shipment of plasma is an obstacle to provision of treatment and care of HIV-1 infected people.